MEMBRANE BIOREACTOR FOR TREATMENT OF RECALCITRANT WASTEWATERS - Suprihatin Suprihatin; Muhammad Romli (Reaktor, 2010)
The low biodegradable wastewaters remain a challenge in wastewater treatment technology. The performance of membrane bioreactor systems with submerged hollow fiber micro- and ultrafiltration membrane modules were examined for purifying recalcitrant wastewaters of leachate of a municipal solid waste open dumping site and effluent of pulp and paper mill. The use of MF and UF membrane bioreactor systems showed an efficient treatment for both types wastewaters with COD reduction of 80-90%. The membrane process achieved the desirable effects of maintaining reasonably high biomass concentration and long sludge retention time, while producing a colloid or particle free effluent. For pulp and paper mill effluent a specific sludge production of 0.11 kg MLSS/kg COD removed was achieved. A permeate flux of about 5 L/m²h could be achieved with the submerged microfiltration membrane. Experiments using ultrafiltration membrane produced relatively low permeate fluxes of 2 L/m²h. By applying periodical backwash, the flux could be improved significantly. It was indicated that the particle or colloid deposition on membrane surface was suppressed by backwash, but reformation of deposit was not effectively be prevented by shear-rate effect of aeration. Particle and colloid started to accumulate soon after backwash. Construction of membrane module and operation mode played a critical role in achieving the effectiveness of aeration in minimizing deposit formation on the membrane surface.